Machining characteristics of micro-magnetic field assisted EDM (µ-MFAEDM). (2020) - Renjith, R.; Paul, Lijo
Abstract: Electric Discharge Machining (EDM) is a thermal process where the substance is removed by a series of electrical emanations happening between an electrode and a workpiece plunged in a dielectric fluid. µ-EDM is a novel machining technique proficient of developing micron-sized features irrespective of material hardness. This process is relevant in the production of miniaturized commodities where industry request for increasingly challenging materials has relinquished the limitations of conventional micromachining techniques. Some precedents include tool steel, tungsten carbide, and titanium used in the manufacture of microscale turning and milling equipment, micro-mould and die making and diesel fuel injector fabrication While EDM, debris particle does form in the machining gap from the eroded materials. If they are not instantly dislodged, arcing occurs and this depreciates the machining efficiency. The introduction of the external magnetic field will facilitate the rapid removal of debris away from the machining gap. The experiment is carried out in an indigenously prepared EDM setup. A magnetic field arrangement is developed in the existing setup to conduct the investigations. The experiment is performed based on Taguchi's L9 series. The investigation is conducted under the voltage range of 35 V, 40 V and 45 V, the frequency of 2 kHz, 4 kHz and 6 kHz and the duty factor of 60%, 70% and 80%. A comparative study is established on the machining characteristics of EDM with MFAEDM.